2011
DOI: 10.1242/jeb.048173
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation in a natural system: Argentine ants solve the Towers of Hanoi

Abstract: SUMMARYNatural systems are a source of inspiration for computer algorithms designed to solve optimisation problems. Yet most 'natureinspired' algorithms take only superficial inspiration from biology, and little is known about how real biological systems solve difficult problems. Moreover, ant algorithms, neural networks and similar methods are usually applied to static problems, whereas most biological systems have evolved to perform under dynamically changing conditions. We used the Towers of Hanoi puzzle to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 42 publications
0
62
0
Order By: Relevance
“…Using the Argentine ant Linepithema humile we previously showed that traillaying ants are efficient at solving the ToH, and are capable of adapting to the modified ToH maze (Reid et al, 2011). Argentine ants were better able to construct one or two shortest paths in the original ToH maze compared with the slime mould, and required a lower number of corrective moves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the Argentine ant Linepithema humile we previously showed that traillaying ants are efficient at solving the ToH, and are capable of adapting to the modified ToH maze (Reid et al, 2011). Argentine ants were better able to construct one or two shortest paths in the original ToH maze compared with the slime mould, and required a lower number of corrective moves.…”
Section: Discussionmentioning
confidence: 99%
“…We used a version of the maze from our study on Argentine ants (Reid et al, 2011), but scaled down to 135mm in length (Fig.1C), the standard Petri dish size used by Nakagaki et al (Nakagaki et al, 2000) in their labyrinth maze-solving experiments with P. polycephalum. We constructed the ToH using acetate on agar substrate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar trail flexibility has been described when traillaying ants face an obstruction of sections of their trail. Reid et al (2011) found that Argentine ants (Linepithema humile) switched to alternative paths in a maze when their initial route was blocked. Laisus niger, another trail-laying ant, used one arm of a two-armed maze when ant densities were low and traffic was free flowing, but switched to using both maze arms when densities increased and trails become congested (Dussutour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%